2014
DOI: 10.5811/westjem.2014.7.18480
|View full text |Cite
|
Sign up to set email alerts
|

BE-SAFE: Bedside Sonography for Assessment of the Fetus in Emergencies: Educational Intervention for Late-pregnancy Obstetric Ultrasound

Abstract: IntroductionLate obstetric emergencies are time critical presentations in the emergency department. Evaluation to ensure the safety of mother and child includes rapid assessment of fetal viability, fetal heart rate (FHR), fetal lie, and estimated gestational age (EGA). Point-of-care (POC) obstetric ultrasound (OBUS) offers the advantage of being able to provide all these measurements. We studied the impact of POC OBUS training on emergency physician (EP) confidence, knowledge, and OBUS skill performance on a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Two studies (total n = 387) showed that both GPs and EPs had 100% accuracy in detecting foetal position in the third trimester [152, 167].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies (total n = 387) showed that both GPs and EPs had 100% accuracy in detecting foetal position in the third trimester [152, 167].…”
Section: Resultsmentioning
confidence: 99%
“…We developed an extensive list of relevant topics within EUS using the ACEP list of ultrasound guidelines and CORD‐AEUS consensus recommendations and input from a group of educationally focused ultrasound faculty (including one program director, EUS fellowship director, and EUS director) and EUS fellows at a large academic EM residency in the central region of the United States 3,8 . After this, we conducted a comprehensive literature review of all clinical applications of ultrasound with the assistance of a librarian to develop a final comprehensive list of applications in Fall 2020 15–55 . The specific search terms are presented in Figure 1.…”
Section: Methodsmentioning
confidence: 99%